Perceived Counseling Support as a Predictor of Young Adults’ Participation in Adult Literacy Programs in Amuwo-Odofin, Lagos State: A Descriptive Survey Study - Rachael Adejoke Ajayi (European Scientific Journal, ESJ, 2026)
Low participation of young adults in adult literacy programmes continues to undermine efforts aimed at improving functional literacy and socio-economic inclusion in Nigeria. This study examined the relationship between perceived counselling support and young adults’ participation in adult literacy programmes in Amuwo-Odofin Local Government Area, Lagos State. Specifically, the study investigated how perceived motivational, psychosocial, and career-related counselling support are associated with attendance, engagement, persistence, and learning motivation. A descriptive survey design was adopted. A structured questionnaire was administered to 300 young adults, of whom 285 returned usable responses. The reliability of the instrument was confirmed with Cronbach’s alpha coefficients ranging from 0.78 to 0.86. Data analysis comprised descriptive statistics, Pearson correlation coefficients, and multiple regression techniques. Results indicated significant positive correlations between perceived counselling support and participation levels, with motivational counselling exhibiting the strongest correlation (r = 0.62, p < 0.01), followed by psychosocial counselling (r = 0.58, p < 0.01) and career counselling (r = 0.55, p < 0.01). Multiple regression showed that these three dimensions collectively accounted for 53% of the variance in participation outcomes (R = 0.73, R² = 0.53, p < 0.001). The study concludes that perceived counselling support is strongly associated with participation outcomes among young adult learners. While the findings reflect statistical associations rather than causal impact, they highlight the importance of supportive learning environments in strengthening adult literacy engagement.